The Egyptian collection at Norwich Castle Museum : catalogue and essays - Kalloniatis, Faye, (Oxbow Books, 2019)
The Egyptian Collection at Norwich Castle Museum' represents the first full publication of this important collection which contains several outstanding objects.0Part 1 begins with an outline of the acquisition history of the Egyptian collection and its display within Norwich Castle in 1894, when it was converted from a prison to a museum. The collection was largely acquired between the nineteenth and first part of the twentieth centuries. 0Part 2 is a detailed catalogue of the complete collection. It is organised into sections with objects grouped together mainly according to type - stelae, shabtis, scarabs, jewellery, amulets, vessels, flints, lamps, inscribed Book of the Dead fragments, metal figurines, and Late Antique cloths; and also according to function - such as cosmetics & grooming, and architectural & furniture elements. The inscribed materials have all been translated and individual entries give examples or parallels. Seventy colour plates illustrate each object.